PENGARUH SKEPTISISME PROFESIONAL, KOMPETENSI, DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS PEMERIKSAAN DALAM PENGAWASAN KEUANGAN DAERAH DENGAN KEPATUHAN PADA KODE ETIK SEBAGAI VARIABEL MODERATING - Turangan, Feibe Maria; Saerang, David Paul .E.; Sondakh, Jullie. J. (Universitas Sam Ratulangi, 2016)
Auditing quality is a complex issue as it deals with so many interfering factors and depends on the viewpoints of each party. The objective of this research is to find out the influence of professional scepticism, competence, independence on auditing quality with complience to the code of ethics as moderating variable at Inspectorate of North Sulawesi Province. The respondents are all the 67 internal auditors Inspectorate of North Sulawesi Province. Inferential statistic has been multiple linear regression analysis (multiple regression) and Moderated Regression Anlyisis (MRA). The results show that professional scepticism have a significant influencing on auditing quality, competence has no significant influencing on auditing quality, independence have a significant influencing on auditing quality, complience to the code of ethics have a significant influencing on auditing quality, professional scepticism is moderated by complience to the code of ethics has no influencing on auditing quality, competence is moderated by complience to the code of ethics has no influencing on auditing quality and independence is moderated by complience to the code of ethics has no influencing on auditing quality. Keywords : Professional skepticism , competence , independence, complience to the code of ethics, auditing quality.